Successful treatment with Omalizumab of a child affected by Systemic Mastocytosis: clinical and biological implications - Grazia Bossi; Valeria Brazzelli; Mara De Amici; Daniela Pietra; Chiara Raviola; Matteo Naso; Corrado Regalbuto; Federica Boselli; Valeria Fortina; Gian Luigi Marseglia (BMC, 2023)
Abstract Background Pediatric Mastocytosis is a rare and heterogeneous disease, characterized by accumulation of mast cells in the skin (Cutaneous Mastocytosis) and/or, less frequently, in other organs, mainly liver, spleen, bone marrow, lymph nodes and gastrointestinal tract (Systemic Mastocytosis). Patients affected by Systemic Mastocytosis show symptoms caused by  a massive release of mast cell mediators: itching, flushing, abdominal pain, generalized weakness, fatigue and neuropsychiatric disorders. Moreover, children with Systemic Mastocytosis are at greater risk of anaphylactic/anaphylactoid reactions, often poorly controlled by the conventional therapy with antihistamines, mast cells stabilizers and steroids. As a result, children affected by Systemic Mastocytosis have a poor quality of life and suffer the consequence of prolonged steroidal treatment. Case presentation A child with Systemic Mastocytosis and severe symptoms, refractory to symptomatic and steroidal therapy, has been successfully treated with Omalizumab, an anti-IgE monoclonal antibody usually employed in allergic patients with severe asthma and orticaria. The onset of clinical benefit of Omalizumab therapy was extraordinarily rapid, but proved to be strictly dependent on drug administration. The child has become completely and steadily asymptomatic. No other anaphylactic episodes have been reported. Steroid treatment could be definitively withdrawn after the second dose of Omalizumab, and all the other medications were later reduced. Twenty months after beginning, Omalizumab therapy is still ongoing with good symptomatology control; no side effects have been observed so far. Conclusions In our experience, Omalizumab is an effective treatment for children affected by Systemic Mastocytosis not responding to conventional medical treatments. The main strengths of this therapy are its rapid and extraordinary efficacy to control the severe mast cells mediator-related symptoms, the lack of side effects and its steroid-sparing effect. However, more extensive and controlled studies in pediatric patients affected by Systemic Mastocytosis are needed to substantiate these promising findings.